The Impact of Local Culture-Based Design Innovation on Sustainable Tourism in Kintamani - Widiyani, Desak Made Sukma; Putra , I Dewa Gede Agung Diasana; Dwijendra, Ngakan Ketut Acwin; Bharuna S, Anak Agung Gde Djaja (Universitas Ibn Khaldun Bogor, 2025)
The study aims to examine the impact of design innovations based on local culture on sustainable tourism in Kintamani. Known for its natural beauty and cultural richness, Kintamani has great potential for sustainable tourism development. Design innovations that incorporate local cultural elements can enhance tourist attractions, enrich visitor experiences, and support the preservation of local culture. The research methods used include both qualitative and quantitative approaches, with data collection through interviews, observations, and questionnaires to gain a deep understanding of the impact of culturally-based design innovations on sustainable tourism in Kintamani. SWOT analysis was applied to identify strengths, weaknesses, opportunities, and threats in the development of tourism in Kintamani. The results of the study indicate that culturally-based design innovations can significantly contribute to sustainable tourism in Kintamani. Development strategies involving collaboration between the government, local communities, and creative industry players are crucial to achieving tourism sustainability in the area. The study concludes that culturally-based design innovations have great potential to support sustainable tourism in Kintamani, provided there is support and active participation from all stakeholders.